Lost in translation: Unlocking planning’s potential to harness social value from property development projects - Nagwa Kady; Sara Özogul; Tuna Tasan-Kok (European Journal of Spatial Development)
Urban planning aims to safeguard public interests and establish norms and principles through spatial regulations to foster social value within communities. However, tools utilized by public planning institutions often fail to align with strategies employed by the property industry to enhance social value in urban development practices. We argue that social values are often lost in translation between public and private realms due to fragmentation at an institutional and project level, impeding effectively harnessing social value objectives. The property industry focuses on social values within specific projects but struggles to connect them to broader public interests. Our research shows that public realms establish social value parameters, yet face challenges due to conflicting perceptions, reduced municipal influence, shifting roles in value implementation, and municipal passiveness. We move beyond dominating narratives of market-driven urban development and entrepreneurial governance arrangements to focus on the interplay between public and private sector actors involved in property development projects. By developing a framework tracing social value creation through development phases: perception, implementation, and operation, we unpack the materialisation of social values through municipal and property industry (inter)actions. Our findings demonstrate the untapped potential of social value for planners to realize societal benefits in property development processes, emphasizing the overlap of public-private interests.